La consolidación de una línea de investigación sobre trauma (2000)
ABSTRACT: In this article, the theoretical foundation of the line of investigation of trauma and the model of several investigations constructed from interdisciplinary and inter-institutional work is described. It was sought to demonstrate the strength of a group of people that are faced with the challenge to investigate a problematic situation in public heath that involves different areas of knowledge. It is the responsibility of everyone to perform directed activities to reduce the incidence and the consequence of trauma that is generating problems in Medellín. It is considered a novel project because it serves to aid education and healthcare and different health professionals, (Physicians, epidemiologists, nursing professionals, health information systems managers, and mental health professionals, among others).